2008
DOI: 10.1038/sj.onc.1210983
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor activation in prostate cancer by three novel missense mutations

Abstract: While epidermal growth factor receptor (EGFR) dysregulation is known to play a critical role in prostate carcinogenesis, there has been no direct evidence indicating EGFR mutations induce tumorigenesis in prostate cancer. We previously identified four novel EGFR somatic mutations in the EGFR tyrosine kinase domain of prostate cancer patients: G735S, G796S, E804G and R841K. In this study, we investigated the oncogenic potential of these somatic mutations by establishing stable clonal NIH3T3 cells expressing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…The mock transfected cells were used as a control (Cai et al, 2008). Similar data were obtained from at least three independent experiments.…”
Section: Matrigel Invasion Assaymentioning
confidence: 53%
“…The mock transfected cells were used as a control (Cai et al, 2008). Similar data were obtained from at least three independent experiments.…”
Section: Matrigel Invasion Assaymentioning
confidence: 53%
“…Interestingly, the samples analyzed belonged to Caucasian, African American and Korean patients, and three of the four mutated adenocarcinomas were from Korean patients. Later on, Cai et al 33 reported that three of these four mutations were constitutively active oncogenic mutations. Schlomm et al 13 also analyzed the EGFR exons 18-21, but did not find mutations, although the number of adenocarcinomas analyzed was very low.…”
Section: Discussionmentioning
confidence: 99%
“…The EGFR gene encompasses 118 kb of sequence on the short arm of human chromosome 7 and contains 28 exons, which encode 1186 amino acids (1). The EGFR protein can be divided into three domains: an extracellular ligand binding domain, a transmembrane domain and an intracellular domain.…”
Section: Introductionmentioning
confidence: 99%